Penerapan Metode Al-Hira’ Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa pada Mata Pelajaran Al-Qur’an Hadis di Kelas VII MTs Babussalam Besilam - Khairuddin YM (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2020)
This study using Al-Hira method to find out and improve seventh grade’s student ability in reading Qur’an especially at MTS Babussalam, Besilam. The subject of this study were 38 of the seventh grade’s student of mts Babussalam Besilam. The aim of this study is to know and increase the student ability in read Qur’an using Al-Hira method. Before Applying Al-Hira method the student ability in read Qur’an still categorized as underprivileged, such as unable to recognize hijaiyah and cannot connect the words of hijaiyah letters. The result was taken from interviews, observations, and student pretest. Sixteen students was pass the test with 42,10% of classical completeness and twenty two student wasn’t pass the test with 57,89% of classical completeness, with 64,73% of average. This research is a classroom action research (CAR) with two cycles. The data was collected by test method and observation in the end of the cycle to find out the improvement of student ability in reading Qur’an using Al-Hira method. After collected and analized the data, twenty four student (63.15%) was pass the test and fourteen student (36.84%) wasn’t pass the test with 73,68% of average in cycle 1. Thirty two student was pass with 84,21% classical completeness. It’s shows, there is 20.78% of classical improvement. Based on the result, it can be conclude that the application of Al-Hira method can improve student ability of reading Qur’an at Al-Qur’an Hadist Subject in seventh grade student of MTS Babussalam, Besilam.